PENERAPAN METODE ADAMS BASHFORTH-MOULTON (ABM) PADA APPROXIMATION JUMLAH PENGUKURAN BIDANG TANAH DI KANTOR PERTANAHAN KOTA LANGSA - Maulana, Shevira Agustri; Sari, Riezky Purnama; Nabilla, Ulya (Program Studi Matematika, Fakultas Teknik, Universitas Samudra. Langsa, Aceh., 2025)
Measuring land plots is the process of determining the location of the boundaries of land plots, which is part of the process of making land title certificates. The number of land plots in the Langsa City Land Office during December 2023 to November 2024 shows a fluctuating pattern. The aim of this analysis is to find out The results of forecasting the number of land plots at the Langsa City Land Office using the Adams Bashforth Moulton method. The data used is land plot measurement data with the type of data being secondary data obtained from the City Land Office Langsa. The type of analysis used is quantitative analysis using the Adams Bashforth Moulton method. The Adams-Bashforth-Moulton (ABM) method is used to determine the forecasting results on the number of measurements of land plots at the Langsa City Land Office. This method starts with an initial solution using fourth order Runge-Kutta, then substituted into the Adams-Bashforth predictor equation and corrected with the Adams-Moulton corrector equation. The iteration is stopped if the relative error is less than 5×10⁻⁷ after 15 iterations at the interval [0,15]. As a result, the number of land plot measurements in Langsa City increases every year, with 62 plots in December 2024, 63 plots in January 2025, 65 plots in February 2025, and 66 plots in March 2025.